The Effect Method of Playing Finger Painting on Creativity Ability And Ability To Espress Languages In Children Age 5-6 Years - Wulansari, Dewi; Masitoh, Siti; Bachri, Bachtiar S. (International Journal for Educational and Vocational Studies, 2020)
This study tries to understand the method of playing finger painting on the ability of creativity and express language of children aged 5-6 years. This research was conducted with a quasi-experimental quantitative method "Pretest-Posttest Control Group Design" in TK Kec. Sukolio Surabaya with a sample of 107 children. Research data obtained through observation, work and documentation, and then analyzed using statistics with ANOVA test with the help of SPSS 25 for Windows. The results showed the  method of playing finger painting   proven  creativity, as evidenced from the Anova test the Fcount value of 187,516 is greater than the Ftable of 3.15. The  method of playing finger painting proven  against express language, as evidenced by the Anova test the Fcount value of 160,922 is greater than the Ftable of 3.15. While  The  method of playing finger painting influences creativity and expresses language, it is evident from the MANOVA test that the Fcount value of 165.122 is greater than the Ftable value of 3.15. Based on the results of data analysis, it can be concluded that  The  method of playing finger painting on creativity and express language for ages 5-6 years, and can develop children's abilities with creativity and language of children aged 5-6 years.